Minutes of the 41st Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
1. Confirmation of Minutes of the 40th Meeting of the Academic Council. 2. Review of the progress and implementation of decisions of the 40th Meeting of the Academic Council. 3. Presentation of Private University Act 2010. 4. Proposal on Minor in Investment Climate management. 5. Proposal on Master of Purchasing and Supply Management. 6. Proposal for Double Major in Applied Physics and Electronics. 7. Updated Curriculum of BS in ECE. 8. Approval for Change in Course Code and Name, ECD Program. 9. Report of Certificate Standardization Committee. 10. Recognition of performance of Antara Debnath Antu (09221195). 11. Proposal from SPH for appointment of ICDDRB researchers as full-faculty of BRACU. 12. Tuition Fee Waiver Policy.